uPATO - A case study - Silva, F. G. M.; Nguyen, Q. T.; Correia, A. F. P. P.; Clemente, F. M.; Lourenço Martins, F. M. (Ultimate Performance Analysis Tool (uPATO), 2019)
This chapter introduces an analysis performed on real data. All described metrics were calculated for both teams and representations were created, using the Web application uPATO. The conclusions obtained from the analysis are then presented.